Donor preparation for germ cell transplantation in giant gouramy: the viability of spermatogonia isolated from giant gouramy cold preserved testis - Irma Andriani; Ita Djuwita; . Alimuddin; Komar Sumantadinata (Syiah Kuala University, 2012)
The recent study has been conducted to develop testicular germ cell (TGC) transplantation as a tool for preservation and propagation of male germ-plasm from endangered fish species. In practice of TGC transplantation,recipient and donor cell may not be immediately available at the same time whereas the testis can not be survive longer when it is outside of the body. Therefore, preservation of testis tissue may be required before transplantation.The research was conducted to evaluate the viability of spermatogonia isolated from short term preserved testis. Testis was preserved in physiological NaCl solution at 4 oC for 6, 12, 24 and 48 hours. Testis were dissociated in 0.5% trypsin and 3% DNase 10 IU/8L in PBS (phosphate buffered solution) complemented with 5% FBS ( fetal bovine serum), 25 mM HEPES and 1mM CaCl2 to obtain testicular germ cell suspension. The testicular germ cells isolated from 24 and 48 hours preservation were performed in trypan blue staining dye (1:1) and the viability of spermatogonia were observed under microscope. The results showed that the viability of spermatogonia started todecrease significantly in 12 hours preservation (P0.05) and up to 48 hours preservation, cell viability was as high as 54,48±8,33%. In conclusion, preserved testicular tissue at 4oC still produced viable spermatogonia that areallowed to use as the source of donor cell for testicular germ cell transplantation of giant gourami.